2002
DOI: 10.1053/rmed.2002.1394
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effectiveness of an asthma educational program: results of a randomized controlled trial

Abstract: Asthma educational programs have been shown to reduce the use of emergency room, frequency of severe asthma attacks and hospitalization. However, its effectiveness in other morbidity parameters and on quality of life has yet to be fully understood. This prospective randomized control trial evaluated the effectiveness of a patient education program in 77 asthmatics according to "Teach Your Patients About Asthma: A Clinicians Guide" (1992). Forty asthmatic patientswere randomly allocated to Group A (usual treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
1
10
1
1
Order By: Relevance
“…NNT values at 1 year of follow-up ranged from 7.7 to 10 in all domains but the ''Emotions.'' These values were higher than what was found in the same cohort 3 months after the education program (from 3.1 to 4.3) (14), suggesting the positive effect of the education program tends to be lost over time. In fact, at 2 years of follow-up, no clinical benefit could be demonstrated.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…NNT values at 1 year of follow-up ranged from 7.7 to 10 in all domains but the ''Emotions.'' These values were higher than what was found in the same cohort 3 months after the education program (from 3.1 to 4.3) (14), suggesting the positive effect of the education program tends to be lost over time. In fact, at 2 years of follow-up, no clinical benefit could be demonstrated.…”
Section: Discussioncontrasting
confidence: 80%
“…Although a positive effect on QoL of education programs lasting for up to 1 year of follow-up has often been reported (4,5,12,14), whether the benefit persists in the long term has seldom been investigated (3,12). Kelso et al (12) and Kauppinen et al (3) demonstrated a QoL improvement lasting for 2 and 5 years, respectively, after an education program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect size was large in both protocols (Table 2), higher in the 14-session protocol. In asthma education programs, improvement in this measure has tended to be minimal (Marabini et al, 2002(Marabini et al, , 2005.…”
Section: Effects On Asthmamentioning
confidence: 99%
“…The effect size for the follow-up assessment (0.9 in the 14-session protocol and 1.1 in the eight-session protocol) was smaller than that reported by O'Byrne et al (d = 2.2) in a multi-center trial of formeterol treatment among asthma patients already taking inhaled corticosteroid therapy, a drug therapy taken by almost all patients in our study. However, no decreases at all are found for albuterol use in several asthma education programs (Grampian Asthma Study of Integrated Care, 1994;Marabini et al, 2002Marabini et al, , 2005Perneger et al, 2002), (where most asthma patients did not have panic disorder, nor did they necessarily overuse bronchodilators), although one study did report a significant decrease in abluterol use (Gani et al, 2001).…”
Section: Measurementioning
confidence: 99%